Composición corporal y somatotipo por posición de juego en balonmano profesional masculino - Ramos-Sánchez, F.; Camina-Martin, M. A.; Alonso-de-la-Torre, S. R.; Redondo-del-Rio, P.; de-Mateo-Silleras, B. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2018)
A cross-sectional descriptive study was accomplished in 19 professional players from Valladolid Handball Club. Anthropometric measurements were performed according to standard protocol. Body fat and bone mass were estimated, and the somatotype was calculated.